English Teachers’ Perceptions on Inquiry Based Teaching - Pokhrel, PremRaj (Journal of NELTA Gandaki, 2021)
This study explores the perceptions of secondary level English teachers on inquiry based teaching. I used phenomenological approach for this study and semi-structured interview was used for data collection which enabled me in capturing the perceptions of purposefully selected participants. The participants were four secondary level English teachers of Rupandehi district. Moreover, this study was based on socio-constructivism theory of Vygotsky. The data were analyzed using descriptive analysis approach. The findings of this study revealed that secondary level English teachers had good perceptions towards using inquiry-based teaching as it enhanced students’ classroom engagement and fostered an effective and meaningful learning experience. The study pointed out a number of opportunities in using inquiry based teaching such as active participation of students, developing discovery skills, the development of critical ability, creativity, problem solving ability, reasoning skills, learners’ autonomy, etc.The findings also indicated that problem in handling technology, lack of motivation and transformation, assessment issues were the challenges while implementing inquiry based instruction in the classroom. The study is expected to have a great significance in improving the 21st century language pedagogy using inquiry based tasks or problems.